Chemical Composition, Free Radicals and Pathogenic Microbes in the Extract Derived from Dictyota dichotoma: In Silico and In Vitro Approaches - Fouad Oumassi; Khalid Chebbac; Naouar Ben Ali; Soundouss Kaabi; Zineb Nejjar El Ansari; Amira Metouekel; Azeddin El Barnossi; Abdelfattah El Moussaoui; Mohamed Chebaibi; Loubna Bounab; Ibrahim Mssillou; Abdelaaty Abdelaziz Shahat; et al. (Marine Drugs)
Marine algae are renowned for their health benefits due to the presence of functional bioactive compounds. In this context, this study aims to valorize the extract of a seaweed, Dictyota dichotoma (D. dichotoma), through phytochemical characterization using liquid chromatography–mass spectrometry (HPLC-MS), as well as in vitro and in silico evaluation of its biological activities (antioxidant and antimicrobial). Phytochemical characterization revealed that the ethanolic extract of Dictyota dichotoma (DdEx) is rich in phenolic compounds, with a total of 22 phycocompounds identified. Antioxidant activity, measured by various methods, showed an IC50 of 120 µg/mL for the DPPH assay, an EC50 of 120.53 µg/mL for the FRAP assay, and a total antioxidant power of 685.26 µg AAE/mg according to the phosphomolybdate (TAC) method. Evaluation of antibacterial activity showed a zone of inhibition diameter ranging from 11.93 to 22.58 mm, with the largest zone observed for the Escherichia coli (E. coli) strain. For antifungal activity, inhibition zone diameters ranged from 22.38 to 23.52 mm, with the largest recorded for the Saccharomyces cerevisiae (S. cerevisiae) strain. The in silico study identified tetragalloyl-glucose, apigenin-7-O-glucoside, and pentagalloyl-glucose as the most active compounds against NADPH oxidase, with docking scores of −7.723, −7.424, and −6.402 kcal/mol, respectively. Regarding antibacterial activity, apigenin-7-O-glucoside, pelargonidin-3-O-glucoside, and secoisolariciresinol demonstrated high affinity for E. coli beta-ketoacyl-[acyl carrier protein] synthase, with docking scores of −7.276, −6.811, and −6.594 kcal/mol, respectively. These in vitro and in silico evaluations showed that D. dichotoma extract possesses antioxidant and antimicrobial properties, due to its richness in bioactive compounds identified by HPLC.